Bi3TaO7 film: a promising photoelectrode for photoelectrochemical water splitting. Issue 1 (3rd December 2019) - Song, Qinggong; Wu, Peidong; Sarkar, Samrat; Zhao, Yufeng; Liu, Zhifeng
Abstract : Most of the transition metal bismuth salts have excellent visible absorption range and carrier transport properties due to their unique structure capable of orbits and s–p bonds. Abstract : Most of the transition metal bismuth salts have excellent visible absorption range and carrier transport properties due to their unique structure capable of orbits and s–p bonds. As one of the transition metal bismuth salts, Bi3 TaO7 is firstly directly prepared on fluorine-doped SnO2 transparent conductive glass (FTO) as a photoanode for photoelectrochemical (PEC) water oxidation via a simple hydrothermal method using a special precursor solution. The growth mechanism of the Bi3 TaO7 film is investigated in detail. Besides, the Bi3 TaO7 photoanode exhibits a wide visible light response range with an optical band gap of 2.88 eV, which is useful for its PEC properties. Bi3 TaO7 achieves an excellent PEC performance by tuning the calcination temperature, producing a photocurrent density of 23.0 μA cm −2 at 1.23 V vs. RHE and showing excellent stability that decays by only 2% after illumination for 6000 s. The above results indicate that Bi3 TaO7 has broad application prospects in the field of PEC water oxidation.